Erectile dysfunction in aging male - Romanelli, Francesco; Sansone, Andrea; Lenzi, Andrea (Acta Biomedica Atenei Parmensis, 2010)
With the increasing longevity in men and women, sexual health concerns have become more and more important and demands for help are far more common than in the past. Erectile dysfunction’s severity and prevalence both increase with aging: since erectile dysfunction is a symptom, physicians should diagnose underlying pathologies that might lead to it instead of focusing on finding a viable treatment. Cardiovascular alterations occur in the elderly, and might lead to erectile dysfunction because of penile blood flow impairment: diabetes, smoking, and sedentary life-style, being risk factors for vascular pathologies, can affect erectile function. Metabolic syndrome and psychological factors are highly prevalent in aging men, and might be other important determinants of erectile dysfunction.Drugs play a role in the pathogenesis of erectile dysfunction, as they can alter hormonal or vascular mechanics needed for achieving or maintaining erection. Alterations in penile vessels can be observed in the elderly: lack of androgens might lead to a reduction of smooth muscle cells content in the penis and an increase in the caliber of vascular spaces. Hypogonadism, when present, should be treated regardless of age; furthermore, synergistic effects have been found during testosterone replacement therapy when using an oral therapy with a PDE-5 inhibitor (sildenafil, vardenafil or tadalafil). These therapies are effective in the elderly, with no increase in the frequency of adverse events, and might also help in providing relief from lower urinary tract symptoms.